2001
DOI: 10.1021/jp011031z
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Transfer Tautomerism of β-Carbolines Mediated by Hydrogen-Bonded Complexes

Abstract: The carboxylic acid catalyzed excited-state amino-imino tautomerism for β-carboline (β-CB) and its analogues has been investigated. Thermodynamics and microsolvation (i.e., stoichiometry of the complex formation) of various β-CB/acetic acid complexes in nonpolar solvents have been studied by means of absorption and emission titration experiments. Supplementary support of the stoichiometric ratio and structure for the hydrogenbonding formation was provided by molecular design and syntheses of various β-CB analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 61 publications
(100 reference statements)
6
23
0
Order By: Relevance
“…The bridging protons produce a single signal, implying an exchange process between the different complexes; this effect can be explained only if we consider a cyclic complex. This cyclic structure is in accordance with the stoichiometric ratios and the formation of hydrogen bond proposed by Chou et al 21 This structure is responsible for the ESPT tautomerism observed for these compounds in different solvents using time-resolved measurements, molecular design and syntheses of different beta-carboline derivatives incorporating only one hydrogen bonding site.…”
Section: Acoh Concentration Effectsupporting
confidence: 88%
See 2 more Smart Citations
“…The bridging protons produce a single signal, implying an exchange process between the different complexes; this effect can be explained only if we consider a cyclic complex. This cyclic structure is in accordance with the stoichiometric ratios and the formation of hydrogen bond proposed by Chou et al 21 This structure is responsible for the ESPT tautomerism observed for these compounds in different solvents using time-resolved measurements, molecular design and syntheses of different beta-carboline derivatives incorporating only one hydrogen bonding site.…”
Section: Acoh Concentration Effectsupporting
confidence: 88%
“…Therefore, this fast excitedstate proton-transfer (ESPT), which takes place through a conduit of relayed hydrogen bonds, is responsible for the emission around 500 nm that traditionally was associated with the fluorescence of zwitterionic species. Nevertheless, like Chou et al, 21 we think 22 -24 that this fluorescence can be attributed to an emission from the tautomer, that we have called D2, resulting from the interaction of N(9)-H and N(2) with two AcOH molecules (Fig. 1).…”
Section: Introductioňmentioning
confidence: 50%
See 1 more Smart Citation
“…order of magnitude to those reported for the ICT states of other compounds, such as 9-aminoacridinium derivatives and N-phenylpyrrole [68,69]. Interestingly, t 0 ICT is also in excellent agreement with the values reported by different authors for the decay time of the zwitterionic phototautomer of betacarboline [22,28,50].…”
Section: Bca-hfipsupporting
confidence: 89%
“…Therefore, the simultaneous presence of several species, which in principle can be formed from the same or different precursors, makes it difficult to separate the different equilibria and to characterize the responsible species. This is the main reason why there is not a complete description of the dynamics of these processes and even controversy between different authors [48][49][50][51].…”
mentioning
confidence: 99%